Rare case of retroperitoneal cystic lymphangioma in an adult - Tandup, Cherring; Chowdhury, Anish; Sakaray, Yashwant Raj; Karthik, Nasika Venkata Kanaka Naga (International Surgery Journal, 2019)
Cystic lymphangioma is benign tumor originating from the lymphatic vessels. Most commonly occurs in childhood and in the head or neck regions, retroperitoneal localization and presentations in adulthood are rare. Making a pre-operative diagnosis is challenging, and only possible subsequent to the histological examination. En bloc resection is the recommended treatment for cystic lymphangioma, and recurrence occurs due to an incomplete excision. We here present a case of 40 year female presenting with progressive palpable lump associated with pain in right quadrant of abdomen, which on computed tomography revealed a large retroperitoneal cystic lesion probably lymphanigoma or cystic mesothelioma.